Antibacterial Porous Electrospun Fibers as Skin Scaffolds for Wound Healing Applications - Lanno, Georg-Marten (ACS Omega, 2020)
[Image: see text] Electrospun fiber scaffolds have a huge potential for the successful treatment of infected wounds based on their unique properties. Although several studies report novel drug-loaded electrospun fiber-based biomaterials, many of these do not provide information on their interactions with eukaryotic and bacterial cells. The main aim of this study was to develop antibacterial drug-loaded porous biocompatible polycaprolactone (PCL) fiber scaffolds mimicking the native extracellular matrix for wound healing purposes. Mechanical property evaluation and different biorelevant tests were conducted in order to understand the structure–activity relationships and reveal how the surface porosity of fibers and the fiber diameter affect the scaffold interactions with the living bacterial and eukaryotic fibroblast cells. Cell migration and proliferation assays and antibiofilm assays enabled us to enlighten the biocompatibility and safety of fiber scaffolds and their suitability to be used as scaffolds for the treatment of infected wounds. Here, we report that porous PCL microfiber scaffolds obtained using electrospinning at high relative humidity served as the best surfaces for fibroblast attachment and growth compared to the nonporous microfiber or nonporous nanofiber PCL scaffolds. Porous chloramphenicol-loaded microfiber scaffolds were more elastic compared to nonporous scaffolds and had the highest antibiofilm activity. The results indicate that in addition to the fiber diameter and fiber scaffold porosity, the single-fiber surface porosity and its effect on drug release, mechanical properties, cell viability, and antibiofilm activity need to be understood when developing antibacterial biocompatible scaffolds for wound healing applications. We show that pores on single fibers within an electrospun scaffold, in addition to nano- and microscale diameter of the fibers, change the living cell–fiber interactions affecting the antibiofilm efficacy and biocompatibility of the scaffolds for the local treatment of wounds.